PENGARUH MASUKNYA PENANAMAN MODAL LANGSUNG TERHADAP PENDAPATAN PAJAK INDONESIA PERIODE 1972-2018 - Rastri Paramita (Pusat Kajian Anggaran, 2020)
The purpose of this study is to determine the short-term and long-term interactions between FDI inflows and the variables controlling trade openness to tax revenues in Indonesia in the 1972-2018 period. In this study using a quantitative method to find out the short-term and long-term interactions between FDI inflows and trade openness to tax revenue. The dependent variable is tax revenue. Whereas the independent variable is FDI inflows. The controlling variable used is trade openness. The method used is the Vector Error Correction Model (VECM), because the data stationer is at first difference but is cointegrated. The results of this study are the short-term and long-term interactions of FDI inflows and controlling variables in the form of trade openness to tax revenue in Indonesia in the 1972 - 2018 period having a positive and significant relationship.